2008
DOI: 10.1097/mjt.0b013e318167180c
|View full text |Cite
|
Sign up to set email alerts
|

Pioglitazone and the Risk of Myocardial Infarction and Other Major Adverse Cardiac Events: A Meta-Analysis of Randomized, Controlled Trials

Abstract: A recent meta-analysis suggested that the use of rosiglitazone increases the risk of myocardial infarction (MI) in patients with type 2 diabetes mellitus. It is unclear whether this is a class effect of thiazolidinediones (TZD). We did a meta-analysis to evaluate cardiovascular outcomes with the use of pioglitazone. Randomized, controlled trials in which pioglitazone was compared with placebo or other hypoglycemic agents were considered for analysis. Studies were included if the data for MI were available. Stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 36 publications
2
17
0
1
Order By: Relevance
“…However, neither did pioglitazone show a favorable effect in reducing the risk of stroke, heart failure or AMI. These findings are in agreement with other studies [9,10,19]. …”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…However, neither did pioglitazone show a favorable effect in reducing the risk of stroke, heart failure or AMI. These findings are in agreement with other studies [9,10,19]. …”
Section: Discussionsupporting
confidence: 83%
“…In addition, different TZDs may not share the same vascular effects. Several clinical trials and observational studies have raised the possibility of increased risk of myocardial infarction and cardiovascular mortality among patients on rosiglitazone [6,7,8,9] but not pioglitazone [8,10,11]. Because of the elevated risk of heart disease, the US Food and Drug Administration has informed the public of restrictions in prescribing rosiglitazone-containing medicines, which have already been suspended in Europe.…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore noteworthy that more attention should be paid to the adverse effect of long-term use of TZDs on the heart of ADPKD patients [39]. Although several studies have confirmed that pioglitazone did not increase the occurrence of cardiovascular events [40], such potential risks cannot be completely excluded, but could perhaps be overcome and minimized by the following measures: (i) strict control of the timing, dose and duration of administration, and avoidance of using the drug in patients with end-stage renal failure or heart failure; (ii) combining the TZD with small doses of the diuretic amiloride (an ENaC inhibitor) to prevent fluid retention; (iii) combining with a V2RA (the diuretic effect may attenuate the adverse effect of rosiglitazone, but attention would need to be paid to its effect on plasma osmotic pressure); and (iv) attempting to use new non-TZD PPAR-γ agonists.…”
Section: Discussionmentioning
confidence: 98%
“…A meta-analysis of 12 clinical trials of metformin as monotherapy or combination therapy and of at least 52 weeks in duration indicated that metformin had no significant effect on CV events versus all comparators (odds ratio [OR], 0.937 [95% CI, 0.820-1.070]; P ¼ 0.339), but did reduce CV events compared with placebo or no therapy (OR, 0.794 [95% CI, 0.644-0.979]; P ¼ 0.031) 13 . In a meta-analysis of five trials of pioglitazone versus placebo or active comparators, the relative risk for myocardial infarction (MI) was 0.86 (95% CI, 0.69-1.07; P ¼ 0.17) and for CV mortality was 0.92 (95% CI, 0.73-1.16; P ¼ 0.47), suggesting that pioglitazone at least does not adversely affect CV outcomes 14 . Findings from studies of exenatide showed similar results.…”
Section: Cardiovascular Risk Reductionmentioning
confidence: 98%